Estrutura de resposta da demanda para redes elétricas rurais e consumidores irrigantes - Uberti, Vinícius André (2022)
Rural grids are composed by radial feeders of great extensions, are located close to the vegetation and, often, in uninhabited places and difficult access locations. In general, rural electrical grids feed seasonal loads, which operate only in the harvest months, and have high levels of technical losses. Often, equipment in these networks is overloaded, as well as the occurrence of transgressions of the operational limits of voltage measurements throughout the grid. Inserted in rural areas, consumers with irrigating rice crops bring their own particularities, such as the lack of automation, direct start of large loads and use of precarious, obsolete or poorly sized equipment, which enhances the reduction in the quality of electricity in these feeders. In this context, this work proposes a demand response structure to rural electricity distribution networks with a concentration of irrigation consumers and proves that demand response can contribute to the quality of energy on these grids, reducing technical losses, improving voltage levels long the grid and avoiding transgressions of operating limits of the equipment. The proposed structure is composed by an irrigating controller, located at the rice farms, and a demand response manager, which is located at the utility operational center. The irrigation controller is developed through the fuzzy logic and considers crop characteristics and weather forecast variables to determine the rotation speed of irrigation equipment. The demand response manager monitors the electrical parameters along the rural feeder and acts on the irrigation controllers, in response to situations of transgression of the rural network's operational limits, like feeders or transformer overload and voltage’s limits transgressions. Results demonstrate technical losses along the grid mean reduction of 27%, as correction of voltage’s precarious situations, and significant reduction of overload occurrence in substation and grid equipment. Another important result occurs in terms of energy efficiency of crop’s irrigation systems, in which energy consumption reductions start from 49%, during off-peak tariff hours, and 18%, during the incentivized tariff hours, even in the most adverse weather and farming conditions.